2017
DOI: 10.1155/2017/6587853
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Malnutrition and Associated Factors among Children in Rural Ethiopia

Abstract: Background Child malnutrition continues to be the leading public health problem in developing countries. In Ethiopia, malnutrition is a leading cause of child illness and death. Recently the composite index of anthropometric failure (CIAF) has been implemented to measure the prevalence of malnutrition. This index presents a more complete picture compared with the previous conventional indices. In this study, CIAF was used to determine the prevalence of malnutrition among children aged 0–59 months in rural Ethi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

59
122
5
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(192 citation statements)
references
References 11 publications
(15 reference statements)
59
122
5
6
Order By: Relevance
“…The household wealth of the family of the subject children was associated with stunted growth in this study. This finding is in line with other findings from analysis of the Mini Ethiopian Demographic and Health Survey data [15], a cross sectional study conducted on prevalence and determinants malnutrition in Bangladesh [13], and another study from Sindh, Pakistan [14]. The primary influence of household wealth is on child feeding practices related to an inadequate amount of food and the nutritional content of meals, which affect the nutritional status of children.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The household wealth of the family of the subject children was associated with stunted growth in this study. This finding is in line with other findings from analysis of the Mini Ethiopian Demographic and Health Survey data [15], a cross sectional study conducted on prevalence and determinants malnutrition in Bangladesh [13], and another study from Sindh, Pakistan [14]. The primary influence of household wealth is on child feeding practices related to an inadequate amount of food and the nutritional content of meals, which affect the nutritional status of children.…”
Section: Discussionsupporting
confidence: 89%
“…This may also indicate educated fathers have a higher awareness and are more conscience of the nutritional needs of children. Other studies in other locations [11,15] found that the educational status of the mother was associated with stunting. This was not the case in our study.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…One community-based study conducted in Bangladesh reported that 48% of rural and 58% of urban area children have undernutrition (Khan & Raza, 2014). This prevalence of CIAF was higher in many developing countries including India (Boregowda, Soni, Jain, & Agrawal, 2015;Dasgupta et al, 2015), Ethiopia (Endris, Asefa, & Dube, 2017), and Nepal (Goswami, 2016) and lower in Tanzania, Zimbabwe, Bolivia, and Peru (Nandy & Miranda, 2008) than the estimate of current study. This study revealed that the undernutrition status was higher among the children when they live in rural settings, if they are in the poorest socio-economic position, if they did not receive any vaccinations, and if they are the firstborn.…”
Section: Discussioncontrasting
confidence: 70%
“…The selection of explanatory variables are theoretically driven that draw support from prior research with regard to factors affecting children's nutritional status. Previous studies are referenced in creating categories for naturally continuous and discrete variables [22][23][24][25][26] ( Table 2).…”
Section: Explanatory Variablesmentioning
confidence: 99%